2019
DOI: 10.1007/s40544-019-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on corrosion resistance and lubrication function of lithium complex grease and polyurea grease

Abstract: In this study, lithium complex grease (LCG) and polyurea grease (PUG) were synthesized using mineral oil (500SN) and polyalphaolefin (PAO40) as base oil, adsorbed onto lithium complex soap and polyurea as thickeners, respectively. The effects of grease formulation (thickener and base oil with different amounts (80, 85, and 90 wt%) on the corrosion resistance and lubrication function were investigated in detail. The results have verified that the as-prepared greases have good anti-corrosion ability, ascribed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 33 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In the last section, the problems about friction and lubrication failures of wind turbine bearings were discussed and analyzed. For decreasing bearing failure problems, it is highly meaningful to improve lubrication technologies for assuring stable operation and longer service life of wind turbine equipment [ 115 , 116 , 117 ]. Better lubrication not only protects the rolling element and the bearing itself by reducing friction, but also avoids corrosion and damage caused by the external environment [ 118 , 119 ].…”
Section: Research On Bearings Lubrication Technology Of Wind Turbinementioning
confidence: 99%
“…In the last section, the problems about friction and lubrication failures of wind turbine bearings were discussed and analyzed. For decreasing bearing failure problems, it is highly meaningful to improve lubrication technologies for assuring stable operation and longer service life of wind turbine equipment [ 115 , 116 , 117 ]. Better lubrication not only protects the rolling element and the bearing itself by reducing friction, but also avoids corrosion and damage caused by the external environment [ 118 , 119 ].…”
Section: Research On Bearings Lubrication Technology Of Wind Turbinementioning
confidence: 99%
“…Ren et al performed a comparative study between lithium‐complex and PU greases regarding their corrosion resistance and lubrication performance. It was shown that for certain base oil (PAO or 500SN Mineral Oil) and thickener (PU or lithium complex) mixture proportions, PU‐based grease mixtures displayed a superior physicochemical and lubrication performance as compared to the lithium complex grease mixtures thus creating a multi‐functional lubricant for extreme conditions 30 …”
Section: Application Of Greases In Ev Industry and Current Challengesmentioning
confidence: 99%
“…The dependence of the structure and properties of the polymer greases on the concentration of lithium stearate was established. Also, the scientific works of the authors [9][10][11][12] are devoted to various aspects of the use of greases in technical applications. At the same time, the analysis of studies has shown that little attention has been paid to the study of the deformation properties of greases under various conditions of tribological contact.…”
Section: Literatuter Reviewmentioning
confidence: 99%